Acupuncture suppresses intravenous methamphetamine self-administration through GABA receptor's mediation. (1st January 2018) - Choi, Yi Jeong; Kim, Nam Jun; Zhao, Rong Jie; Kim, Da Hye; Yang, Chae Ha; Kim, Hee Young; Gwak, Young S.; Jang, Eun Young; Kim, Jae Su; Lee, Yun Kyu; Lee, Hyun Jong; Lee, Sang Nam; et al.
Highlights: Acupuncture at HT7 suppressed the intravenous methamphetamine self-administration behavior. Effects of Acupuncture were blocked by GABA receptor antagonists. C-Fos expression in the nucleus accumbens were in parallel with the behavioral data. Acupuncture inhibits the intravenous methamphetamine self-administration, at least in part, via GABA receptor system. Abstract: Objectives: Methamphetamine is one of the widely abused drugs. In spite of a number of studies, there is still little successful therapy to suppress the methamphetamine abuse. Acupuncture has shown to attenuate the reinforcing effects of psychostimulant. Based on, the present study investigated if acupuncture could suppress intravenous methamphetamine self-administration behavior. In addition, a possible neuronal mechanism was investigated. Materials & methods: Male Sprague-Dawley rats weighing 270–300 g were trained to intake food pellet. After catheter implantation, animal was trained to self-administer methamphetamine (0.05 mg/kg) intravenously using fixed ratio 1 schedule in daily 2 h session during 3 weeks. After training, rats who established baseline (infusion variation less than 20% of the mean for 3 consecutive days) received acupuncture treatment on the next day. Acupuncture was performed at each acupoint manually. In the second experiment, the selective antagonists of GABAA or GABAB receptor were given before acupuncture to investigate the possible neuronal involvement of GABA receptor pathway in the acupuncture effects. C-Fos expression was examined in the nucleus accumbens to support behavioral data. Results: Acupuncture at HT7, but not at control acupoint LI5, reduced the self-administration behavior significantly. Also, the effects of acupuncture were blocked by the GABA receptor antagonists. C-Fos expression was shown to be parallel with the behavioral data. Conclusions: Results of this study have shown that acupuncture at HT7 suppressed methamphetamine self-administration through GABA receptor system, suggesting that acupuncture at HT7 can be a useful therapy for the treatment of methamphetamine abuse.